Church history is dead, long live historical theology! - Houston, Peter (HTS teologiese studies, 2020)
Church history is dead, long live historical theology! This restatement of the monarchical law of le mort saisit le vif is at once a statement of irreparable discontinuity and assumed continuity. The old monarch is no more, yet a new and different monarch ascends to fill the same vacant throne. This is the paradox of church history becoming historical theology. Reviewing the work of W.A Dreyer and J. Pillay on the re-imagining of church history as historical theology, this article explores the tension between the demise of church history as a subject in South Africa and the emerging understanding and application of historical theology, arguing that more can be made of trans-disciplinary dialogues.